SEXUAL SADISM AS EXPERIENCED BY LISBETH SALANDER IN STIEG LARSSON’S THE GIRL WITH DRAGON TATTOO - DEA ANISSA RAHMAT (LITERA KULTURA : Journal of Literary and Cultural Studies, 2014)
SEXUAL SADISM AS EXPERIENCED BY LISBETH SALANDER IN STIEG LARSSON’S THE GIRL WITH DRAGON TATTOO Dea Anissa Rahmat English Literature, Faculty of Languanges and Arts, Surabaya State University dearbepe@gmail.com Drs. Much. Khoiri, M.Si English Literature, Faculty of Languanges and Arts, Surabaya State University much.khoiri@yahoo.com Abstrak Sadisme dalam seksualitas adalah perasaan gairah seksual yang disebabkan oleh pemberian rasa sakit, penderitaan, dan penghinaan kepada orang lain. Perilaku sadisme yang nampak secara langsung dan terang-terangan dalam pencapaian titik klimaks perilaku seks seseorang dapat dijadikan indikator bahwa orang tersebut mengalami penyimpangan. Penyimpangan seks dalam kasus sadisme sering mengalami penurunan signifikasi dan fungsi akibat perilaku menyimpang dalam berfantasi. Orang yang menjadi mitra atau objek yang dikenai perilaku sadis dalam hubungan seks belum tentu menjadi rekan yang bersedia. Jika kegiatan seks yang identik dengan perilaku sadis ini disetujui oleh kedua pihak ataupun hanya seorang saja, maka dapat diartikan pihak yang melakukan kegiatan tersebut mengalami kegagalan seksual secara normal dan perlu alternatif lain untuk mencapai titik klimaks. Misalnya, melakukan aktifitas kekerasan pada saat berhubungan. Dalam kajiannya, peneliti sengaja mengambil novel dengan judul The Girl With The Dragon Tattoo untuk menganalisis perilaku menyimpang dalam hubungan seks yang dialami oleh tokoh Salander. Teori yang digunakan untuk menganalisis perilaku menyimpang dalam tokoh utama dalam novel berasal dari teori Sigmund Freud tentang psikologi dan kepribadian. Dengan dilengkapi teori relevan, penelitian ini mengambil beberapa kutipan dalam novel yang mewakili perilaku menyimpang dalam seksualitas untuk dijadikan data dalam kajian peneliti. Hasilnya, perilaku menyimpang dalam seks ditunjukkan oleh tokoh Lisbeth Salander dalam novel memberikan dua hipotesis. Pertama, dalam novel muncul beberapa sadisme seksual yang terjadi pada rekan tokoh Bjurman yang teridentifikasi dari data berupa kutipan teksnya. Salander sebagai korban sadisme seksual dari pengacara rekan Nails Bjurman. Kedua, beberapa faktor yang berkontribusi Lisabeth Salander untuk melakukan sadisme seksual. Penelitian ini mencerminkan pengalaman deskriptif sampel perempuan yang terlibat dengan perilaku sadisme seksual beserta faktor-faktor yang berkontribusi dibaliknya. Keywords: Sexual sadism, sadistic behavior, The Girl with The Dragon Tattoo Abstract Sexual sadism is a feeling of sexual excitement resulting from administering pain, suffering, or humiliation to another person. When sadism becomes directly and overtly related to sexual gratification, they are considered perversions. Sexual sadism often experiences significant impairment or distress in functioning due to actual sadistic behaviors or sadistic fantasies. With regard to actual sadistic behavior, the person receiving the pain, suffering, or humiliation may or may not be a willing partner. Whether or not the partner is consenting, it is the very real suffering they are experiencing that is arousing to the sadist. This study examines Stieg Larsson’s The Girl With The Dragon Tatttoo, which is about sexual sadism as experienced by Salander. This study uses theory of sexual sadism and Sigmund Freud’s theory of Psychology and Personality. By using relevant theories, the study analyses the data—i.e. quotations from the novel that represent sexual sadism. The result of this analysis shows that sexual sadism experienced by Lisbeth Salander as reflected in Steig Larsson’s The Girl With The Dragon Tattoo can be described by two parts. First, it shows that there are several sexual sadism which occurs from her guardian Bjurman. Salander as a victim of sexual sadism from the guardian laywer Nails Bjurman. Second is to reveal the factors that contributed Lisabeth Salander to do sexual sadism. It is about a descriptive experiences of a sample of women who have been consensually involved with sexual sadism and factors that contribute to sexual sadism. Keywords: Sexual sadism, sadistic behavior, The Girl with The Dragon Tattoo INTRODUCTION In human sexual life, there are certain conditions of sexual disorder which consider as embarassing and dangerous situations from the society’s point of view. Normally, sexual activity is the union of the female and male’s genital and other sexual activity besides it is taken as “abnormal”. Few examples of sexual deviations are: homosexual, masochism, sadism, necrophilia, fetishism, etc (Barlow, 2009: 364). Sadism implies pleasure in inflicting. When sexual sadism is applied to show fantasies, urges or behaviors that involve real acts in which the suffering of another person is found sexually exciting. The essential feature of sexual become directly related sexual gratification. That sexual gratification it considered perversions. Sadism is a feeling of sexual excitement resulting from administering pain, suffering, or humiliation to another person. The pain, suffering, or humiliation inflicted on the other is real, it is not imagined and may be either physical or psychological in nature. A person with a diagnosis of sexual sadism is sometimes called a sadist. The name of the disorder is derived from the proper name of the Marquis Donatien de Sade (1740-1814), a French aristocrat who became notorious for writing novels around the theme of inflicting pain as a source of sexual pleasure. The sadistic acts performed or fantasized by a person with sadism often reflect a desire for sexual or psychological domination of another person. These acts range from behavior that is not physically harmful although it may be humiliating to the other person (such as being urinated upon), to criminal and potentially deadly behavior. Acts of domination may include holding or imprisoning the partner through the use of handcuffs, cages, chains, or ropes. Other acts and fantasies related to sexual sadism include paddling, spanking, whipping, burning, beating, administering electrical shocks, biting, urinating or defecating on the other person, cutting, rape, murder, and mutilation. Psychopathia Sexualis, later defined sadism as: "The experience of sexual, pleasurable sensations (including orgasm) produced by acts of cruelty, bodily punishment afflicted on one's person or when witnessed in others, be they animals or human beings. It may also consist of an innate desire to humiliate, hurt, wound or even destroy others in order, thereby, to create sexual pleasure in one self". This kind of sexual sadism has appeared in the literature (Kraft-Ebing, 1886: 274) . One of the writers that written about sexual sadism in a novel is Stieg Larsson. The novel was released to great acclaim in Sweden and later, on its publication in many other European countries. In the original language, it won Sweden's Glass Key Award in 2006 for best crime novel of the year. It also won the 2008 Booke Prize, and in 2009 the Galaxy British Book Awards for Books Direct Crime Thriller of the Year, and the prestigious Anthony Award for Best First Novel. Larsson was posthumously awarded the ITV3 Crime Thriller Award for International Author of the Year in 2008. The Girl with the Dragon Tattoo debuted at number four on The New York Times Best Seller list. The novel received mixed reviews from American critics. In a review for The New York Times upon the book's September 2008 publication in the United States, Alex Berenson wrote, "The novel offers a thoroughly ugly view of human nature"; while it "opens with an intriguing mystery" and the "middle section of Girl is a treat, the rest of the novel doesn't quite measure up. The book's original Swedish title was Men Who Hate Women, a label that just about captures the subtlety of the novel's sexual politics." The Los Angeles Times said "the book takes off, in the fourth chapter: From there, it becomes classic parlor crime fiction with many modern twists....The writing is not beautiful, clipped at times (though that could be the translation by Reg Keeland) and with a few too many falsely dramatic endings to sections or chapters. But it is a compelling, well-woven tale that succeeds in transporting the reader to rural Sweden for a good crime story."Several months later, Matt Selman said the book "rings false with piles of easy super-victories and far-fetched one-in-a-million clue-findings."Richard Alleva, in Commonweal, wrote that the novel is marred by "its inept backstory, banal characterizations, flavorless prose, surfeit of themes (Swedish Nazism, uncaring bureaucracy, corporate malfeasance, abuse of women, etc.), and--worst of all author Larsson's penchant for always telling us exactly what we should be feeling." Discussing and analyzing about character or human, they cannot be separated from personality terms. Personality derives from the Latin word persona, which refers to a mask used by actors in a play. The character is easy to see how persona came to refer to outward appearance, the public face we display to the people around us. Personality refers to the characteristics patterns of behavior and ways of thinking that determine a person’s adjustment to his environment. The personality of somebody has built from the experiences that they got from the social surrounding and also the genetic factor gives the background of someone’s personality Schultz (2009: 8). The direct influences of sexuality on personality comes from the effects of sex hormones. It influences body build, body functioning, and the quality of the individual behaviour. The indirect influence comes up from three sources: the effect of cultural influences sex drive, the attitudes of significant people and their treatment to the individual caused by sexuality, also the molding of personality pattern of sex appropriatenes, which admitted by society. To understand the aspect of psychology within literary work, needed psychology of literature, it is used to investigate the psychology aspect, which shown by the character within the novel The Girl with Dragon Tattoo by Stieg Larsso. Wellek and Werren (1989: 81) stated psychology of literature, mean the psychological study of the writer as type and as individual, or the study or creative process, or the study of the psychological types and laws present within works of literature, or, finally, the effects literature upon its readers (audience psychology). Sigmund Freud emphasizes how early stage of childhood is important part to create someone’s adulthood personality and behavior. He says that part of our personality is formed on the basis of the unique relationships we have as children with various people and objects. Accordingly we develop a personal set of character attributes, a consistent pattern of behavior that defines each of us as an individual (Shannon, 2009: 64). Grossman (1991) states the psychological effects trauma, wheteher in infancy or adult life, are best understood in connection with the development and functioning of the capacity to fantasize. Here, a child which has been experienced physical and psychological trauma can build a fantasy refers to the violence.Violence can be in the form of hitting, slamming, humiliating, and so on. Consequently, a child can imagine that she/he is happy if he/she hurts and or being hurt by another people. This kind of fantasy can cause sexual sadism behaviour. In accordance of background study above, it can be simplify to discuss among two problems that emerge as significant concern toward this novel. How is sexual sadism as experienced by Lisbeth Salander reflected in Steig Larsson’s The Girl With Dragon Tattoo? What factors contributed Lisabeth Salander to do sexual sadism in Stieg Larsson’s The Girl With Dragon Tattoo? This study will uses two theories which are in line with the statement of the problems.The first is about review of related literature which contains the theories that are used in the analysis. In this chapter, the concept of sexual sadism and will be related to the concept of sexual sadism and theory of personality. The second will deal with the core of the study, which is the analysis of the study. The last chapter of this study is the conclusion as the result of the analysis. The additions will be added and got along with the analysis such as appendix, which consists of the biography of the author of this novel, and the synopsis of the novel. Those additions are to be the closing of this study. RESEARCH METHOD Research methodolgy that used in this analysis here must be qualified as an applying in literary appreciation. The thesis is regarded as a descriptive-qualitative study and uses a library research. This study uses novel of Stieg Larsson entitled The Girl with The Dragon Tattoo that published Seven Stories Press, 140 Watts Street, New York in 2007 as the data source of this study. The data are in the form of direct and indirect speech of the characters, dialogues, epilogues and quotations which indicate and represent aspect of power abuse and sexualization which is experienced by the main character. This thesis is using the library method in collecting the data. It does not use the statistic method. That is why it is not served in numbering or tables. Library research used an approach in analyzing this study. The kind of library research which is used here is intensive or closely reading to search quotations or phrases. It also used to analyze the literary elements both intrinsic and extrinsic. The references are taken from library and contributing ideas about this study from internet that support the idea of analyzing. The analysis is done by the following steps: (1) Classification based on the statement of the problems. This classification is used to avoid the broad discussion. There are two classifications in this study. (2) Describe the reflection of Sexual sadism as experienced.(3) To reveal the factors that contributed Lisabeth Salander to do sexual sadism in Stieg Larsson’s The Girl With Dragoon Tattoo.The quotations that showed how the character’s sexuality is affected by his power are taken as data. (4) Drawing the conclusion based on the analysis which is in line with the problems. ANALYSIS The first section is about the analysis of sexual sadism as experienced by Salander. The experience of Salander in sexual sadism is started when she meets her new guardian lawyer. Sexual sadism happened when she has an interview with Bjurman just after he became her guardian. Bjurman, on the other hand is recognize as a person who likes to do sex by sentence that is written in the novel. Salander is uncomfortable with Bjurman question and she feels that it is not her business by asking about sex in some kind of an interview. Salander’s statement proves it. “No, it’s not particulary nice to be fucked in the arse but what the hell business is it of yours?” ... She left his office with a feeling of disgust. (Larsson, 2008: 220) The statement that Bjurman has no business with Salander sexual background, even he asks her impolitely. His authority is all about Salander legal powers, no more than that. Salander, moreover, express her disgust feeling to him after she feels that Bjurman was going too far. It can be concluded that she feels uncomfortable with Bjurman’s questions. Salander thinks that it is not his right to ask her those questions. Then, she has been decided that she does not like Bjurman by leaving his office. The sex that is done by Bjurman is not like the sadist thing that he will do to Salander. He does some enjoyable acts to make Salander comfortable and feel horney. The nice thing is also given to her so she enjoyed the sex because Bjurman has a plan to have a sex with her again. The sex act done by Bjurman can be seen in quote below. He stood behind her. Suddenly he was massaging the back of her neck, and he let one hand slide from her left shoulder across her breasts. He put his hand over her right breast and left it there. When she did not seem to object, he squeezed her breast. Salander did not move. She could feel his breath on her neck as she studied the letter opener on his desk; she could reach it with her free hand (Larsson, 2008: 241). The incident happened when Salander comes to Bjurman office ask money to buy new computer, since her old laptop broken caused by an accident. She does not get the money easily because Bjurman forces her to do something. Bjurman assaults her by touching her breast. The quotation shows that Bjurman sexual sadism her by touching and squeezing her breasts. This is the one of sexual part that shows from the novel. Salander did nothing with all what Bjurman has already done to her. She got one lesson from Holger Palmgren that when there was an impulsive actions led to trouble, and trouble could have unpleasant consequences. Salander will never do anything without first weighing the consequences. In that quotation stated Salander feeling towards Bjurman. She has plan to use the letter opener as th weapon to fight againts him. Sexual sadism has formed her to be a person not easy to back down, she would always take revenge to all forms of act that try to hurt her. However, her status limits her to do that. Even, Salander cannot do something because she needs the money. All that she thinks is about the consequences. Bjurman starts to say what adult usually says which one another are known what the conversation means is. “I think you and I are going to be a good friend,” he said. “we have to be able to trust each other.” When she did not replay he said: “you’re a grown woman now, Lisbeth” She nooded. “Come here,” he said and held out his hand. (Larsson, 2008: 242) Salander just fixed her gaze on the letter opener for several seconds before she stood up and went over to him. In her heart, she says, consequences. It means that she knows the consequences by having such a lawyer guardian. The real acts that lead to sex activity are shown by Bjurman. The statement is explained bellow. He took her hand and pressed it to his crotch. She could feel his genitals through the dark gabardine trousers. While said, “If you’re nice to me, I’ll be nice to you.” He puts his other hand around her neck and pulled her down to her knees with her face in front of his crotch. (Larsson, 2008: 242) It is shown that Bjurman rapes to her. In this case, he forces to suck his genital or can be called as oral sex. At the time she is just thinking that she did it for the money. In this case, Bjurman makes it difficulty to Salander in getting her money. In addition Bjurman treat her by saying: “If you’re nice to me, I’ll be nice to you,” he repeated. “If you make trouble, I can put you away in an institution for the rest of your life. Would you like that?” (Larsson, 2008: 243) In this case, Salander cannot do anything to protect herself. She said nothing if Bjurman only gives words in order to treat Salander, without caring with Salander answer about his question, he continues the sex to Salander. He waited until she lowered her eyes, in what he regarded as submission. Then he pulled her closer. Salander opened her lips and took him in her mouth. He kept his grip on her neck and pulled her fiercely towards him. She felt like gagging the whole ten minutes he took to bump and grind; when finally he came, he was holding her so tight she could hardly breathe. (Larsson, 2008: 243). From the quotation above, it is clearly stated how Salander is forced to suck her guardian genital. He places his genital in Salander’s mouth in order to get satisfied. Salander passively action towards those kinds of sadism makes Bjurman thinks more to hurt her. It is supported by (Krafft-Ebing, 2008: 14) that Sadism in sexual pleasurable sensations (including orgasm) produced by acts of cruelty, bodily punishment afflicted on one’s own person or when witnessed in others, be they animals or human beings. The additional terrifying expression is shown by Salander in the quotation bellow. She realized with terrifying clarity that she was out of her depth. (Larsson, 2008: 273). It makes Salander in dead feeling. She thinks that Bjurman is doing something so serious and injury. What can help Salander this time is only keeping the pain that she gets? In another situation Bjurman turn mad and crazy. By taking metal stuffs that Salander hear from the sound of the clanking. The clanking sound of metal shows that Bjurman begins to do the sexual sadism, beside he says the words to treat Salander. The quotation is show at below: “You have to learn to trust me, Lisbeth,” he said. “I’m going to teach you how this grown-up is played. If you don’t treat me well, you have to be punished. When you’re nice to me, we’ll be friends.”( Larsson, 2008: 274) From the quotation above Salander seems not to do anything. She only does what Bjurman wants and the only thing that she can feel is sick and gets more pain by Bjurman. Bjurman do not stop his act to Salander. In another situation, Bjurman asks Salander wheather she likes to do anal sex or not by asking “So you don’t like anal sex, he said”(Larsson, 2008: 274). The more Salander keep silence, the more he maltreats her. Anal sex is the act of sexual by putting something in someone anus. It is really dangerous for someone’s health or even can caused a great injury to victim. He also starts the sadism acts along sexual activity. The quotation below shows his sadist act that Bjurman does to Salander. Salander opened her mouth to scream. He grabbed her hair and stuffed the knickers in her mouth. She felt him putting something around her ankles, spread her legs apart and tie them so that she was lying there completely vulnerable. She heard him moving around the room but she could not trough the T-shirt around her face. It took him several minutes. She could hardly breathe. Then she felt an excruciating pain as he forced something up her anus. (Larsson, 2008: 274) The using of metal stuffs are cannot be tolerated anymore. The sadist action in sexual is real happening to Salander. Stuffed the knickers in Salander mouth is an act that hurt Salander physically. Bjurman spreads her legs apart and ties her so that she is completely vulnerable. Those acts are considered as physical sadism that she gets when having sex with Bjurman. Salander is completely pain of being sadistic by Bjurman when they having sex. It is shown when she felt an excruciating pain as forced something up her anus. Bjurman must do something to her anus that makes Salander in total pain. Beside, Bjurman did more and more tricks so that he could release his sadism along the act that he applied to Salander. Bjurman is going crazy more than before. The acts that Bjurman has done is supported by Matsumoto (2009: 490) theory about sexual sadism that defines sexual sadism is a paraphilia in which sexual arousal occurs as the result on inflicting physical or mental pain on another person as a means of exercising control over him or her. It means that the sadist feels pleasure and lust when he/she sexual partner suffered. Thus she/he can show his/her domination and power. Then, the second section will show factors contributed Salander to do sexual sadism. Then, the second section will show the factors that contributed Lisabeth Salander to do sexual sadism. This chapter will apply the theory in chapter two as the base theory, and hopefully this analysis will not deviate from the theory that has been explained before. Bjurman, now, has responsible for Salander’s assets and financial, but he handles it out of his authority. He is a corrupt guardian that used Salander victim. He opened a new account in her name, and she was supposed to report it to Milton’s personal office and use it from now on. The good old days were over. In future Bjurman would pay her bills, and she would be given an allowance each month. He told her that expected her to provide receipts for all her expenses......”This had to do with the fact that i’m responsible with for your mone,” he said. “You have to put money aside for the future. But don’t worry; I’ll take care all of that.” (Larsson, 2008: 182) The quotation above shows that how Bjurman make Salander financially dependent happen is done by Bjurman. Although he is responsible for her assets and financial, but he handle it out of his authority. He is a corrupt guardian that used Salander victim. It is totally different with the precede guardian who let her free to manage her own money even though her status still under guardianship. Since, Bjurman is a corrupt, he take over and fully contol Salander money. He does not let Salander free access to use her money. Even, he force Salander to open a new account in a bank and requiring the victim to justify all money spent, so that Bjurman can control it. Besides, the statement in the quotation, “You have to put money aside for the future. But don’t worry; I’ll take care all of that”(Larsson, 2008: 182). Support the fact that Bjurman has abuse her financial as well. It is found that his life is to be a guardian of mentally disturbed likes Salander. He lives in her prosperity which is comes from his clients assets or money. He uses their weakness in legal status power, so that he is easily corrupt their money. Their weakness in legal status would make them afraid and do nothing about it. Obviously, it is form of economical as factor. The second form of economical that is done by Bjurman towards Salander is that by withholding the money or the access to the money. It is a complicated for Salander to ask her money, even for buying food. She has to work and Bjurman easily take over the money. It is prove by this quotation. Bjurman moved back to his side of the desk and sat on his comfortable leather chair. “I can’t hand out money to you whenever you like,’’ he said. “Why do you such an expensive computer? There are plenty of cheaper models that you can use for playing computer games.” “I want to have control of my own money like before.” Bjurman gave her a pitying look. (Larsson, 2008: 242) The quotation clearly stated can be concluded that Bjurman has underestimates her by saying that she did not need such sn expensive computer. It means that she is only a stupid girl that needs a computer just for playing games. Here, how Bjurman make a difficulty for Salander to get her money. He always ask or even demand her to do something first before she get the money. In this case, he would give Salander money after he takes advantages from her in terms of satisfying him by oral sex and anal sex, touching her breasts, and so forth. On the one hand, Bjurman has been abuse Salander by those various forms of violence. On the other hand, he has been abuse his profession as a guardian who is supposed to be protect the client. Here, he is withholding Salander own money that supposed to be her rights. Her authority is only take over Salander assests and financial so that the money can be used in a right way. However, Bjurman has been corrupted the money give some terms for her in getting her own money. Thereby, Bjurman has already one other forms ef economical as factor towards Salander. In the next meeting with Bjurman, Salander really need to buy a food. All the money that is kept by Bjurman is locked. It such the difficult thing to get the money like she must kill him first then she will get her own money. Psychological sadism is always given by the prepetator in order to treath the victims so they agree to do the sexual sadism. Psychological sadism also happen in the process of the sex itself in order to make the victims cannot avoid the prepetator to do sadism along the sex process. This is shown by Salander that she agree when Bjurman treat her to be nice with him. A threat could make the victim afraid psychologically. If the victim feels afraid with threat of the perpetrator, so they will be easily to do what they want to the victim. You have to learn to trust me, Lisbeth,’’ he said. “i’m going to teach you how this grown-up game is played. If you dont treat me well, you have to be punished. When you’re nice to me, we’ll be friends (Larsson, 2008: 274) The quotation above shows Salander is threatened by Bjurman. After force to suck his genital, he threat her not to tell anyone about that. Salander just keep silence because she is feels afraid about the consequences related with her status if she reports it. He treats her as a whore not as a girl under his protection. In supported by Freud who insisted his sexual theory applied to all mental illness. However, in this moment, Bjurman not only threats her but he has done threatening harm. It is stated that threat and hurt her b slap and grip chin tight. It can be concluded that combine sadism always happened to Salander. Salander is not only facing of psychological but also accompanied by physical. The same thing also happened to her which is done by Bjurman. In another hand, the personality of somebody is built from the experiences they got from the social surrounding and also the genetic factor gives the background of someone’s personality. Part of our personality is formed on the basis of the unique relationships we have as women with various people and objects. We develop a personal set of character attributes that defines each of us as an individual. The personality of Salander is considered as having a bad image. In her life, she likes to do dangerously violent things made her caught up by the police. One of her acts is explained below: When she turned fifteen, the doctors had more or less agreed that she was not, after all, dangerously violent, nor did she represent any immediate danger to herself. (Larsson, 2008: 174) Salander, in her life, she does not only danger someone near with her but also herself. Such of her bad behavior is leading her personality as a bad teenage. In other situation she has troubles with surrounding and herself by consuming alcohol and drug abuse. She builds an image that she has the negative attitude toward anybody and herself. It is said by Salander that the sex world is nothing new for her. It happens because she has already done the sex with more than ten people in her teen age. It is supported by the information she had had over fifty partners since the age of fifteen that she totally sex players. It is shown that by doing such of the sex activities will make her impression that going to be judge by other person. This is supported by Schultz (2009: 8) that based on its derivation, we might conclude that personality refers to our external and visible characteristics, those aspects of us that other people can see. Our personality would then be defined in terms of the impression we make on others that is, what we appear to be. In short, our personality may be the mask we wear when we face the outside world. CONCLUSION The analyzing of sexual sadism in Stieg Larsson’s The Girl with Dragon Tattoo has give better understanding about several forms of sexual sadism as experienced that occurs and factors contributed Lisabeth Salander to do sexual sadism . Through the thesis analyzing, is is found that Salander has suffered from several forms of sexual sadism. As explained above that Salander as the main character experiences some forms sexual sadism, they are physical sadism, psychological and factor that contribute to do sexual sadism, they are threat and economical The conslusion of research question 1 are sexual sadism as experienced by salander is as an object. She gets both physical and psychological experiences by Bjurman asher guardian lawyers. She gets pain and suffer from physical experience. While in pysichological experience, she gets treatments from Bjurman. These are the conslusion of research question 2. The factors that make Salander to do the sexual sadism are unbelieveable because not all people want to be an object of sexual sadism. They are pyschology, personality, and economic factors. The psychology is like trearments that Bjurman has given to her and the personality is when Salander has such a bad personality backgrond, like havinh sex with many people. Finally, economic is the main factor for Salander to sexual sadism because if she wants to get her money, she must do the sex with Bjurman which bring her to sexual sadism. In Stieg Larsson The Girl with Dragon Tattoo, we can see Salander gets some forms of sexual sadism from Bjurman. There is not only sexual insult verbal, but also some kinds of sexual sadism of rape forms. The experience of Salander in sexual sadism is started when she meets her new guardian lawyer, Bjurman. On the other hand is recognize as a person who likes to do sex in the novel. Bjurman takes an opportunity by keeping Salander account and if she wants to get the money she must do the sex with him first. It is also supported by interview that is done, Bjurman asks about Salander sex life which is turn out to be another interrogation by asking her private aspect in her life, is that about her sexual background. All she wanted is about the money without making and giving any sexual sadism with him. With all scare feeling she agrees to do it again with Bjurman. The thing that she hates so much is having sex with a condition and compulsion. The fear is appears on Salander body language. This sexual sadism has made Salander suffered from some physically. It has become the worst experience ever in her life. Sexual sadism which is experienced by Salander is mostly done by Bjurman. Bjurman is not only doing the sexual sadism toward Salander in form of rape, but also psychological. In this case, Salander can be concluded to get she witnesses and watching other person, or even the person that she like, suffered from physical sadism. In this novel, Salander has been found experiencing sexual sadism. REFERENCES Barlow, H. David, Durand. V. Mark. 2009. Abnormal Psychology 5th edition. USA : Wadsworth Cengage Learning. Hoeksema, Susan Nolen. (2004). Abnormal Psychology. Third edition. New York: McGraw-Hill Comapanies Inc. Krafft-Ebing, Richard von. 1933. Psychopathia Sexualis: With Especial Reference to the Antipathic Sexual Instinct: A Medico-Forensic Study. New York: Physicians and Surgeons Book Co. Larsson, Stieg. (2008). The Girl with Dragon Tattoo. New York: Vintage Books. Matsumoto, David. 2009. The Cambridge Dictionary of Psychology. USA: Cambridge University Press. Schultz, D. P. & Schultz, S. E. (2009). Theories of personality 9th Edition. United States of America:Wadsworth Cengange Learning. Shannon, Joyce Brennfleck. 2009. Theories of Personality 9th Edition. United States of America: Omnigraphics, Inc.